FIELD GEOLOGY OF GUBI AREA, NORTHEASTERN NIGERIA - Rufai, F.A; Halilu, M.; Ahmed, H.A; Bukar, M. (IJRDO-Journal of Applied Science, 2017)
Basement rocks of the Gubi area of Northeastern Nigeria were assessed and found to comprise of Pre-Cambrian basement rocks invaded by Pan-African granites generally referred to as the ‘Older Granites’. The area was composed mainly of Migmatite gneiss, granite gneisses and calcalkaline granites. The tectonic structures in the study area trend mostly NE – SW and subordinately NW-SE and N-S conform with the regional deformational structures which occurred during the Pan African thermotectonic events in the Nigerian basement.